Terpaan Media Sosial dalam Membentuk Gaya Hidup Mahasiswa - Mega Ayu Muliana Saragih; Ai Wanda Wulandari; Dziaul Muaimi; Maulana Andinata Dalimunthe; Hasan Sazali (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
Based on the observations made, the campus should be a place for students to gain knowledge, exchange ideas, socialize with fellow students, and so on. However, what is seen is that the campus is used as a place to show off their appearance and lifestyle. So that when many students adopt a consumptive lifestyle, campus life is increasingly unclear. Students who have the ability in terms of finance become easily influenced to fulfill this consumptive lifestyle. This type of research is field research or often known as field research. Field research is a research conducted in the field or at the research location, a place chosen as a location to investigate objective phenomena as they occur at that location. Based on the results of the study, it can be concluded that social media is a medium that allows users to carry out social activities with each other through the internet network without being limited by distance, space, and time. Students use social media such as Instagram, WhatsApp and Facebook. Social media has become a lifestyle for students